APLIKASI METODE COMMON REFLECTION SURFACE (CRS) UNTUK MENINGKATKAN HASIL STACK DATA SEISMIK LAUT 2D WILAYAH PERAIRAN “Y” - Hirafiany Daruartati; Agus Setyawan; Istiqomah Ari Kusuma (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Stacking is an important phase in the seismic data processing, it’s a tool or quick look before subsurface section resulted. Common Reflection Surface is the developing of the conventional processing that has been generally done. CRS method has more benefits than conventional stack method, specially on the complex structure and do not rely on from velocity model that’s really useful for seismic data processing. The main difference between CRS and conventional stacking mode is on stack parameter decision or the attribute connected to subsurface reflector. CRS application has been applied in the area “Y” using software ProMAX 2D. In this research by using marine seismic data has done five times using different apperture values, they are 150 m, 100 m, 67 m, 33 m, and 20 m for getting the best stack result. Based on the research can be concluded that CRS method has applicated successly on the 2D marine seismic data having a better result than by using conventional method, proved by CRS method stack result can show the better reflector continuity and it increases the signal to noise ratio qualitative.